PP277 Analysis Of The Current Situation Of Using Hospital-Based Health Technology Assessment In Kazakhstan. (December 2020) - Avdeyev, Andrey; Kaptagayeva, Aigul; Benberin, Valeriy; Shanazarov, Nasrulla; Makalkina, Larissa; Hailey, David
Abstract : Introduction: Hospital-based health technology assessment (HB-HTA) in Kazakhstan is currently at the initial stage of development. The Medical Center Hospital of the President's Affairs Administration, Nur-Sultan is one of the first examples of implementing and using an HB-HTA system in practice, having included in its structure an HB-HTA unit in 2015. Methods: In order to evaluate the current situation of using the principles of HB-HTA in Kazakhstan hospitals, a special questionnaire was developed. The questionnaire was sent in the form of an official request on behalf of the Ministry of Health Care. An official response was received from twenty-nine hospitals, of which nine were at the federal level, thirteen at the regional level, and seven at the city level. Results: Of the twenty-nine hospitals that participated in the survey, only half (52%) indicated that they were aware of the principles of using the HB-HTA system and of the structure and functions of mini-health technology assessment reports (55%). Nonetheless, most hospitals (90%) noted that the results of HB-HTA may affect the final decision on implementing new technologies in practice, and that using the systematic approach of technology assessment is necessary. Conclusions: In assessing the clinical and economic effectiveness of new health technologies in hospitals, and the viability of implementing them, there is a lack of standardized processes in managerial decision making. The assessment of clinical effectiveness and safety when implementing technologies is carried out mainly by technology applicants or by the main specialists who are responsible for the profile of evaluating technology. This can be regarded as a conflict of interest, since the applicant's wish to introduce the new technology may bias the evaluation process.